Penerapan Metode Multisensori Berbantu Balok Hurup Dalam Meningkatkan Kemampuan Membaca Siswa Disleksia Di Sekolah Dasar Inklusi - Yuli Yuli Mulyawati (FOUNDASIA, 2022)
The ability to read is very important in life, because by reading we can find various information through various writings that are given to us by other people. By reading we can improve our knowledge skills with reading literacy in various ways. Obstacles in reading greatly affect students' cognitive abilities. Where should be reading, students are able to reason about various things in learning. However, if there are problems with just reading, it is very possible that this interferes with other things related to the learning process. There are several things that can cause students to experience reading difficulties. There are reading difficulties caused by students who suffer from dyslexia. Dyslexia in general is a learning disorder in children characterized by difficulty reading and writing. The main causative factor is the brain. But it could also be due to psychological, biological and educational factors seen from the way of learning. And to handle it, special treatment is needed for children who have dyslexia. In class 2, SDN Bantar Jati 9, Bogor City, there are students who have indications of dyslexia. The method in this research is qualitative with a case study approach. The results of the study show that the efforts made to improve the reading ability of dyslexic students are by applying the Multisensory Method. In the implementation of the application of the multisensory method requires learning media that can assist in the learning process, based on the results of research the appropriate media is to apply block letters media. The results showed that the application of the multisensory method assisted by letter blocks can improve the reading ability of dyslexic students. The conclusion is that the application of the multisensory method assisted by letter blocks is effective.